Proceedings and recommendations of the National Webinar on Implementation of Access to Plant Genetic Resources and Benefit Sharing - Paroda, R.S.; Agrawal, Anuradha; Rana, J.C.; Brahmi, Pratibha; Archak, Sunil; Varaprasad, K.S.; Mal, Bhag; Singh, Rakesh; Dsouza, Sonal; Sarath Babu, B. (Bioversity International and the International Center for Tropical Agriculture, 2020)
A National Webinar on “Implementation of Access to Plant Genetic Resources and Benefit Sharing (ABS)” was held on August 27, 2020. The meeting was co-organized by UN Environment Implemented GEF Project, Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT), Delhi Office, India and the Indian Society of Plant Genetic Resources (ISPGR) and was attended by 200 stakeholders from academia, policy, management, farmers and private sector. This document provides briefly the deliberations held during the webinar and the major recommendations which emerged.